2021
DOI: 10.3390/ijms22137093
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Leukemic Stem Cells in Chronic Myeloid Leukemia: Is It Worth the Effort?

Abstract: Chronic myeloid leukemia (CML) is a classical example of stem cell cancer since it arises in a multipotent hematopoietic stem cell upon the acquisition of the t(9;22) chromosomal translocation, that converts it into a leukemic stem cell (LSC). The resulting BCR-ABL1 fusion gene encodes a deregulated tyrosine kinase that is recognized as the disease driver. Therapy with tyrosine kinase inhibitors (TKIs) eliminates progenitor and more differentiated cells but fails to eradicate quiescent LSCs. Thus, although man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 133 publications
0
16
0
Order By: Relevance
“…Targeted agents targeting the above molecules or pathways have shown promising efficacy in eliminating LSCs by enhancing the killing effect of TKI on LSCs in vitro and vivo studies. Several promising strategies have also entered clinical trials, and some preliminary results showed that TKIs in combination with IFNa, JAK2 inhibitors, PPAR-g agonists, BCL-2 inhibitors, and lysosomotropic agents have the potential to improve treatment response in CML (169,170).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…Targeted agents targeting the above molecules or pathways have shown promising efficacy in eliminating LSCs by enhancing the killing effect of TKI on LSCs in vitro and vivo studies. Several promising strategies have also entered clinical trials, and some preliminary results showed that TKIs in combination with IFNa, JAK2 inhibitors, PPAR-g agonists, BCL-2 inhibitors, and lysosomotropic agents have the potential to improve treatment response in CML (169,170).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%
“…The role of mir-21 in TKIs resistance in CML is further supported by Wang and colleagues' report that mir-21 inhibition by antagomiR-21 sensitized LSCs to IM treatment by increasing imatinib-induced apoptosis [173,174]. In addition to mir21, miR-30a is also reported to be associated with TKIs' inability to eliminate quiescent LSCs [173].…”
Section: Mirnas Role In Resistance To Tkis and Blast Crisis Progressionmentioning
confidence: 79%
“…The interaction between LSCs and stromal cells present in the bone marrow niche where they reside is well established and seems to support LSCs maintenance in bone marrow despite TKI treatment [174]. Although miR-126 was described as a pro-leukemic miRNA in acute myeloid leukemia (AML), BCR-ABL1 was demonstrated to downregulate miR-126 in CML.…”
Section: Mirnas Role In Resistance To Tkis and Blast Crisis Progressionmentioning
confidence: 99%
“…Furthermore, CD93, as a major integrin α5β1 mediator, along with CD44 can bind to fibronectin [ 45 , 46 ] and might have a role in LSC adherence within the BM niche [ 37 , 44 ]. Although CD93 is consistently and selectively expressed on CML LSCs, it can also be found on other cell types such as platelets and endothelial cells; therefore, CD93 is unlikely to serve as a therapeutic target, while it can be used as a prognostic biomarker to differentiate CML patients at high risk for molecular relapse after treatment discontinuation [ 47 ]. The possible profile of LSCs in CML could be Lin − CD34 + CD38 − CD45RA −/Low , CD117 (KIT) − , CD26 + , and CD90 + that are identified as potential therapeutic targets at a single-cell level with a higher proliferative and colony-forming potential than normal HSCs [ 37 , 48 ].…”
Section: Properties Of CML Lscsmentioning
confidence: 99%
“…It seems that they are likely to have less toxic or off-target effects than inhibitors of factors essential for the survival of LSCs. However, unlike AML, CAR cell therapies have not been significantly developed in CML so far [ 42 , 47 ]. Targeting surface markers particularly overexpressing on CML LSCs such as IL1RAP, CD26, CD44, CD70, and CD123 has demonstrated a powerful antileukemic effect in preclinical CML studies (Table 1 ), although the viability of some of them in the treatment of patients with CML needs to be further investigated, including anti-CD44 agents with regard to the expression of CD44 on HSCs [ 179 ] .…”
Section: Therapeutic Implications Of CML Lscsmentioning
confidence: 99%